IMPACT OF TRAUMATIC BRAIN INJURY ON SMALL INTESTINAL MORPHOLOGY: AGE-DEPENDENT CHANGES IN LYMPHOID STRUCTURES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This study investigates the morphological changes in the small intestine following traumatic brain injury (TBI) in rats, focusing on the impact of varying injury severity and the role of lymphoid structures within the mucosa. TBI is known to have widespread systemic effects, and this research aims to understand its influence on the gut's structural integrity, particularly in the mucosal immune response. The study examines changes in the small intestine across different age groups (1, 6, and 18 months) of Wistar rats, utilizing histological and morphometric methods to assess the severity of damage and its impact on lymphoid tissue. The findings reveal that TBI leads to significant changes in the small intestine, with varying degrees of inflammation, necrosis, and lymphoid follicle formation depending on injury severity and the age of the rats. Notably, treatment with L-lysine showed promising results in mitigating some of the morphological changes. These findings suggest that TBI-induced changes in the small intestine, particularly in its immune structures, have important implications for digestive and immune system functions, and may inform future therapeutic strategies for TBI patients.